Stone Tool Manufacture Strategies and Lithic Raw Material Exploitation in Coastal Patagonia, Argentina: A Multivariate Approach. (21st November 2013) - Cardillo, Marcelo; Alberti, Jimena
Abstract : This paper seeks to characterize strategies of artifact manufacture and lithic raw material exploitation along San Matías Gulf coast, Argentina, using multifactorial and cluster analysis. Multifactorial analysis is a relatively new method that has yet to be used for archaeological analysis; it has the advantage that it allows us to describe data using different groups of qualitative or quantitative variables at the same time. Additionally, cluster analysis was conducted on multifactorial axis in a bid to identify grouping patterns. The results obtained from the combination of these two methods suggest that they may be useful in characterizing technological strategies in the study area. Furthermore, they may also be a powerful exploratory and characterization tool able to generate explanations at low spatial scales. The application of these methods on San Matías Gulf study case suggests that along the western and northern coasts of this Gulf the most important variables in determining differences in resource use were the fragmentation ratio and lithic raw materials used in artifact manufacture.